تعليمية إعراب الجمل لتلاميذ مرحلة الرابعة متوسط ـ دراسة ميدانية ـ - شريط، آية; شراحي، ايمان; سواكر، ثورية; نيد، ذكرى; شنطابي، هدى (University of Eloued جامعة الوادي, 2025)
يعُد إعراب الجمل مهارة أساسية لتحليل الجمل وفهم بنيتها ،لكن تلاميذ السنة الرابعة متوسط يواجهون صعوبات في ذالك ، وجاءت المذكرة بعنوان "تعليمية إعراب الجمل لتلاميذ السنة الرابعة متوسط " دراسة ميدانية لتقديم شرح مفصل من جهة نظرية وتطبيقية ،وتهدف إلى تحسين مستوى التلاميذ وتسهيل فهمهم لإعراب الجمل وتم تقسيمها إلى فصلين : النظري بعنوان المفاهيم الأساسية للبحث ، والفصل التطبيقي بعنوان دراسة الميدانية للإعراب الجمل عند تلاميذ الرابعة متوسط ، وتعتمد المذكرة على المنهج الوصفي في جانب النظري ،والمنهج الوصفي وتحليلي في الجانب التطبيقي ،وأسفرت الدراسة عن كون تعليم إعراب الجمل يجب أن يكون مبنيًا على التدرج ،الفهم ،وتطبيق العملي ،مع اعتماد أمثلة قريبة من بيئة المتعلم، واستخدام استراتيجيات متنوعة تنشط الحصص وتُبسط المفاهيم ، وبذالك يمكن الرفع من أداء التلميذ في هذا المجال ، مما ينعكس إيجابا على نتائجه في اللغة العربية عموما . Sentence expression is a basic skill for analyzing sentences and understanding their structure, but fourth-year students face difficulties in this. The memo entitled "Sentence education for fourth-year students" was a field study to provide a detailed explanation from a theoretical and practical point of view, and aims to improve the level of students and facilitate their understanding of the expression of sentences. It was divided into two chapters: theoretical entitled basic concepts for research, and the applied chapter entitled Field study of sentence expression among fourth-mediate students. The memo depends on the descriptive method in the theoretical aspect, and the descriptive and analytical method in the practical aspect. The study resulted in the fact that the teaching of sentence expression should be based on gradation, understanding, and application Practical, with the adoption of examples close to the learner's environment, and the use of various strategies that activate classes and simplify concepts, thus raising the student's performance in this field, which reflects positively on his results in the Arabic language in general.
مذكرة ليسانس..2025